Aspects of computational thinking in unplugged activities with origami and mathematics - Graciolli, Carolina Yumi Lemos Ferreira [UNESP]; Rocha Junior, Romario Costa da [UNESP]; Silva, Ricardo Scucuglia Rodrigues da [UNESP] (Univ Nove Julho, 2022)
The article aims to present some of the existing relationships between origami and computational thinking and how they can complement each other and serve as mutual support. A contextualization about the art of paper folding is presented, as well as some understandings about computational thinking, specifically its four pillars: decomposition, algorithm, pattern recognition and abstraction. As a possibility, we resort to unplugged activities involving instructions for folding animals and geometric solids that can be developed both in Elementary School and in High School or Undergraduate Degree. Finally, it is shown that the proposals can enable the development of the four pillars of computational thinking. Thus, it can be noted that the activities described open possibilities for computational thinking when worked in consonance with origami.
Keywords: Mathematics education; Paper folding computacional thinking; Geometric solids